Pengaruh Perencanaan Pajak dan Modal Intelektual terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI periode 2021 - Amalia, Alviona Rizka; Umaimah, Umaimah (Universitas Muhammadiyah Gresik, 2023)
The objective of this research is to examine the influence of Tax Planning and Intellectual Capital on Firm Value. The target population for this study comprises manufacturing companies that are publicly listed on the Indonesia Stock Exchange during the 2021 timeframe. The sample was selected using a purposive sampling technique, resulting in a total of 92 companies being included with a 1-year observation period. This research adopts a quantitative approach and utilizes secondary data. The analysis technique employed isi multiplei lineari regressioni analysis. Thei findingsi ofi thisi studyi demonstratei thati intellectuali capitali hasi ai significanti impact on firm value, whereas tax planning does not affect firm value. Type of Paper: Empirical Keyword: Tax Planningi, Intellectual Capitali, Firm Valuei, Manufacturing Company